2002
DOI: 10.1590/s0102-311x2002000600015
|View full text |Cite
|
Sign up to set email alerts
|

Sexualidade de mulheres vivendo com HIV/AIDS em São Paulo

Abstract: The social and cultural setting which increases female vulnerability to HIV does not disappear when women living with HIV/AIDS discover that they are infected. Following diagnosis, new challenges arise in their emotional lives, an issue which has received little attention in the literature. This study interviewed 1068 women living with HIV/AIDS using a questionnaire consisting of both open and closed questions, aimed at describing aspects of their sexual and reproductive lives and how they perceive counseling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
1
36

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 6 publications
5
17
1
36
Order By: Relevance
“…From this perspective, the desire or the decision to have children, depending on the normative concepts in which this takes place, may deserve different "levels of acceptability", even if there is an awareness of the risk of vertical HIV transmission. This could be seen from the modulations in the meanings of such risk that the interviewees presented, and it is in accordance with the studies by Paiva et al 16,17 In the light of the foregoing, a certain degree of polarization was demonstrated between the search for "technical control" over the disease, through emphasis on the epidemiological risk of vertical transmission, and people's plans for their lives, which included the assertion of identities and the strengthening of conjugal alliances by means of maternity and paternity.…”
Section: "We Already Thought (Of Having Children) But the Slips Thatsupporting
confidence: 91%
See 1 more Smart Citation
“…From this perspective, the desire or the decision to have children, depending on the normative concepts in which this takes place, may deserve different "levels of acceptability", even if there is an awareness of the risk of vertical HIV transmission. This could be seen from the modulations in the meanings of such risk that the interviewees presented, and it is in accordance with the studies by Paiva et al 16,17 In the light of the foregoing, a certain degree of polarization was demonstrated between the search for "technical control" over the disease, through emphasis on the epidemiological risk of vertical transmission, and people's plans for their lives, which included the assertion of identities and the strengthening of conjugal alliances by means of maternity and paternity.…”
Section: "We Already Thought (Of Having Children) But the Slips Thatsupporting
confidence: 91%
“…1,9 Research among seropositive women in Brazil has indicated that around 30 to 40% 15, * of them knew of their HIV diagnosis before becoming pregnant. ** Regarding information on vertical HIV transmission, Paiva et al 16,17 showed that approximately 75% of the women and 50% of the men had this information, although their desire to have children did not present any significant correlation with the level of information.…”
mentioning
confidence: 99%
“…Alguns estudos têm apontado esse mesmo padrão de comportamento, cuja base é o modelo monogâmico com pressuposição de fidelidade dos parceiros; embora os homens se sintam mais protegidos da aids no casamento do que as mulheres (Paiva, 2002;Silva e Vargens, 2009;Lopes e col., 2007;Sousa e col., 2008). Nossos resultados mostram que para as mulheres a palavra fidelidade ganha outro sentido na relação.…”
Section: Discussionunclassified
“…Nos centros de referência, encontramos profissionais que espelham valores e significados para o sexo e para a Aids em que foram socializados, em geral conservadores, estigmatizadores daqueles com opções diferentes da sua. Encontramos, também, profissionais que se identificam com valores mais abertos à diversidade, mas que muitas vezes tratam a conduta sexual como irresponsavelmente culpada porque "não usou a camisinha", como se fazer sexo seguro dependesse sempre da vontade e da razão informada, acusando os que não absorvem adequadamente ("desconsideram") os guias para a proteção do sexo (Paiva et al, 2001).…”
Section: Paiva Vunclassified